Akad Ijarah Muntahiya Bi Al-Tamlik (IMBT) at Sharia Financial Institutions Perspectives of Classical and Contemporary Ulema - Hardiati, Neni; F, Fitriani; Fauziyah, Ida (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The emergence of the Ijarah Muntahiya Bittamlik contract is also an innovation. However, it has also become a polemic because of the merger of contracts. In this article, the analysis of the Akad Ijarah Muntahiya Bittamlik is described from the Opinion of the Ulama with descriptive methods and normative juridical approaches, the author uses several literature sources, so that it can be categorized as library research. The results show that Islamic economic experts, both contemporary economic thinkers such as Adimarwan, Al-Mujamma' Al-Fiqhi, and classical scholars such as Hanabillah, Malikiyah, Shafi'iyah and Hanabalah, the law of the IMBT contract is mubah (permissible).